Cell-to-cell spread of HIV-1 and evasion of neutralizing antibodies. - Schiffner, T; Sattentau, Q; Duncan, C (2013)
Cell-to-cell spread of human immunodeficiency virus (HIV-1) between immune cells was first observed over 20 years ago. During this time, the question of whether this infection route favours viral evasion of neutralizing antibodies (NAbs) targeting the virus envelope glycoprotein (Env) has been repeatedly investigated, but with conflicting results. A clearer picture has formed in the last few years as more broadly neutralizing antibodies have been isolated and we gain further insight into the mechanisms of HIV-1 transmission at virological and infectious synapses. Nevertheless consensus is still lacking, a situation which may be at least partly explained by variability in the experimental approaches used to study the activity of NAbs in the cell-to-cell context. In this review we focus on the most critical question concerning the activity of NAbs against cell-to-cell transmission: is NAb inhibition of cell-to-cell HIV-1 quantitatively or qualitatively different from cell-free infection? Overall, data consistently show that NAbs are capable of blocking HIV-1 infection at synapses, supporting the concept that cell-to-cell infection occurs through directed transfer of virions accessible to the external environment. However, more recent findings suggest that higher concentrations of certain NAbs might be needed to inhibit synaptic infection, with important potential implications for prophylactic vaccine development. We discuss several mechanistic explanations for this relative and selective loss of activity, and highlight gaps in knowledge that are still to be explored.